Preparation of heterogeneous phthalocyanine catalysts by cotton fabric dyeing - Sevim, Altuğ Mert; Ilgün, Cidal; Gül, Ahmet (Elsevier BV, 2011)
Abstract Metal-free ( 2 ) and metallo-phthalocyanines ( 2a–d ) bearing four thioglycolic acid groups on the periphery were prepared by cyclotetramerization of a new precursor, namely 4-(carboxymethylsulfanyl)phthalonitrile ( 1 ) in the presence of the corresponding divalent metal salts (Zn(II), Co(II), Ni(II), Cu(II)). The new compounds were characterized by elemental analyses, IR, UV–Vis, mass, 13 C-NMR and 1 H-NMR techniques. All these newly synthesized water-soluble metallo-phthalocyanine derivatives were supported on cationic cotton fabrics and the washing and water fastnesses of these novel dyed fabrics were investigated. Washing and water fastness data suggested that cationic cotton fabrics are superior to the others when dyed with these metallo-phthalocyanines.